2016
DOI: 10.1158/2326-6066.cir-15-0096
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy against Metastatic Melanoma with Human iPS Cell–Derived Myeloid Cell Lines Producing Type I Interferons

Abstract: In recent years, immunotherapy for advanced melanoma has been gaining increased attention. The efficacy of anti-cytotoxic T-lymphocyte antigen 4 antibodies, anti-programmed cell death 1 antibodies, and the BRAF V600E kinase inhibitor has been proven in metastatic melanoma. At the same time, adoptive cell transfer has significant effects against metastatic melanoma; however, it is difficult to apply on a broad scale because of the problems related to cell preparation. To overcome these problems, we developed im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…We previously showed that type I IFN introduced iPS-ML increased the expression of CD169, a marker of M1 macrophages, that can activate antitumor immunity. We also confirmed the infiltration of iPS-ML expressing type I IFN into the tumor nests [7]. Taken together, we believe that immune cell therapy with both iPS-ML-41BBL and iPS-ML expressing type I IFN can overcome the immune-resistant tumor microenvironments, such as types II, III, and IV.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We previously showed that type I IFN introduced iPS-ML increased the expression of CD169, a marker of M1 macrophages, that can activate antitumor immunity. We also confirmed the infiltration of iPS-ML expressing type I IFN into the tumor nests [7]. Taken together, we believe that immune cell therapy with both iPS-ML-41BBL and iPS-ML expressing type I IFN can overcome the immune-resistant tumor microenvironments, such as types II, III, and IV.…”
Section: Discussionsupporting
confidence: 76%
“…The benefits of using iPS-ML are its infinite proliferative capacity and ease of genetic modification. We have previously used iPS-ML as effector cells and reported the effectiveness of type I interferon-expressing iPS-ML against some cancers [6,7]. Type I interferon delivery by iPS-ML elicits antitumor immunity via XCR1 + dendritic cells [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…iPSDM-based cell therapeutics have been studied mainly in cancer 42, 43 and airway diseases 44 using murine models particularly relating to the protective benefits of macrophage-mediated phagocytosis. The intraperitoneal injection of iPSC-derived myeloid cells 10 genetically engineered to express interferon-β significantly inhibited the growth of human gastric and pancreatic cancers implanted in the peritoneal cavity, 42 as well as inhibiting the growth of disseminated human melanoma cells in immunocompromised SCID mice.…”
Section: Drug Testing and Cell Therapeuticsmentioning
confidence: 99%
“…The intraperitoneal injection of iPSC-derived myeloid cells 10 genetically engineered to express interferon-β significantly inhibited the growth of human gastric and pancreatic cancers implanted in the peritoneal cavity, 42 as well as inhibiting the growth of disseminated human melanoma cells in immunocompromised SCID mice. 43 iPSC-derived primitive macrophages intranasally transferred to the lung matured into alveolar macrophages and eliminated the surfactant protein accumulated as a result of Csf2ra deficiency in mice. 44 Indeed, evidence is emerging that iPSC-derived myeloid cells may have specific advantages as in cell therapeutics.…”
Section: Drug Testing and Cell Therapeuticsmentioning
confidence: 99%